AB0511 INTERNATIONAL CONSENSUS ON ANCA TESTING AND INTERPRETATION BEYOND SYSTEMIC VASCULITIS. (2nd June 2020) - Moiseev, S.; Cohen Tervaert, J. W.; Arimura, Y.; Bogdanos, D.; Elena, C.; Damoiseaux, J.; Ferrante, M.; Flores-Suárez, L. F.; Fritzler, M.; Invernizzi, P.; Jayne, D.; Jennette, J. C.; et al.
Abstract : Background: ANCA can be detected in sera from patients with autoimmune, inflammatory, infectious or neoplastic diseases. Objectives: To issue a Consensus Statement on ANCA testing and interpretation beyond systemic vasculitis. Methods: This Statement was prepared by a group of experts, based on the results of a comprehensive search in PubMed. Results: In certain settings beyond systemic vasculitis, ANCA may have diagnostic, clinical, and/or prognostic relevance. Testing for PR3- and MPO-ANCA by specific immunoassays should be performed in any patient with clinical features suggesting ANCA-associated vasculitis and in patients with anti-GBM disease and idiopathic interstitial pneumonia. Routine ANCA testing is not recommended in patients with connective tissue diseases (CTD), autoimmune liver diseases, inflammatory bowel diseases, infections, and/or malignancy unless there is evidence for small vessel vasculitis. ANCA testing by specific immunoassays may be useful in patients with rheumatoid arthritis, systemic sclerosis or primary Sjögren's syndrome who have kidney disease with a nephritic sediment or in patients with systemic lupus erythematosus if a kidney biopsy shows prominent necrotizing and crescentic lesions or proliferative lupus nephritis. ANCA testing may be justified in patients with suspected autoimmune hepatitis type 1, who do not have conventional disease-related autoantibodies, or in patients with inflammatory bowel diseases in case of diagnostic uncertainty to discriminate ulcerative colitis from Crohn's disease. In these cases, ANCA should be tested by indirect immunofluorescence since target antigens are not well characterized. ANCA against bactericidal/permeability-increasing protein may be a biomarker for deteriorating lung function and a poor prognosis in patients with cystic fibrosis. Conclusion: ANCA testing is clinically relevant not only in patients with manifestations suggesting systemic vasculitis, but also in patients with certain other disorders, particularly in patients with anti-GBM disease or idiopathic interstitial pneumonia. Disclosure of Interests: Sergey Moiseev Grant/research support from: This work was supported by the 5-100 Project, Sechenov University, Moscow, Jan Willem Cohen Tervaert: None declared, Yoshihiro Arimura: None declared, Dimitrios Bogdanos: None declared, Csernok Elena: None declared, Jan Damoiseaux: None declared, Marc Ferrante: None declared, Luis Felipe Flores-Suárez: None declared, Marvin Fritzler: None declared, Pietro Invernizzi: None declared, David Jayne Grant/research support from: ChemoCentryx, GSK, Roche/Genentech, Sanofi-Genzyme, Consultant of: Astra-Zeneca, ChemoCentryx, GSK, InflaRx, Takeda, Insmed, Chugai, Boehringer-Ingelheim, J. Charles Jennette: None declared, Mark Little: None declared, Stephen P. McAdoo: None declared, Pavel Novikov Grant/research support from: This work was supported by the 5-100 Project, Sechenov University, Moscow, Charles D. Pusey: None declared, Antonella Radice: None declared, Alan D. Salama: None declared, Judith Savige: None declared, Mårten Segelmark: None declared, Yehuda Shoenfeld: None declared, Renato Alberto Sinico: None declared, Maria Jose Rego de Sousa: None declared, Ulrich Specks: None declared, Benjamin Terrier: None declared, Athanasios Tzioufas: None declared, Severine Vermeire: None declared, Ming-hui Zhao: None declared, Xavier Bossuyt: None declared